PERCEPTION OF NURSING ABILITY IN IMPROVING MOTIVATION AND HOPE IN HYPERTENSION PATIENTS IN HOSPITALS IN EAST JAWA - Windu Santoso; sri sudarsih (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2019)
Hypertension is one of the important factors as a trigger for non-communicable diseases. Hypertension is a preventable and controllable disease that can be managed with medications and lifestyle changes. The purpose of this study was to determine perceptions of Nurse Ability to Increase Expectations and Motivation of Hypertensive patients. The type of research used is cross-national survey. The Population in this study were all nurses in hospitals in East Java who had been fully accredited. The sample amounted to 200 nurses with a simple random sampling sampling technique. The research instrument uses a questionnaire that has been tested for validity and reliability. Perception of Nurse's Ability in Increasing Expectations and Motivation of Hypertension Patients in Hospitals in East Java is an important matter that is equal to 75.7%. This shows the importance of nurses' ability to increase motivation and expectations of patients suffering from hypertension.